2021
DOI: 10.20473/jkl.v13i1.2021.35-40
|View full text |Cite
|
Sign up to set email alerts
|

The Outbreak of Hepatitis A: Evidence in Pacitan District

Abstract: Introduction: Indonesia is a country with a high geographical distribution of hepatitis A. In June 2019, the government established the status of hepatitis A outbreaks in Pacitan District, which is spread across several districts. Based on data from the District Health Office of Pacitan, there were 1,310 peoples with hepatitis A on October 2019. Through this study, the relation between knowledge, attitudes, and personal hygiene as risk factors of hepatitis A outbreaks in Pacitan District can be identified. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Our findings showed a spike in hospitalised paediatric hepatitis A patients in 2016 and 2019. This was in accordance with the outbreak in Pacitan district in 2016 11 and Surabaya in 2019 12 , Indonesia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings showed a spike in hospitalised paediatric hepatitis A patients in 2016 and 2019. This was in accordance with the outbreak in Pacitan district in 2016 11 and Surabaya in 2019 12 , Indonesia.…”
Section: Discussionsupporting
confidence: 86%
“…Our laboratory analysis found that MLR and BUN may be an indicator of hepatitis A severity as these values were significantly higher in the prolonged group. The urea synthesis capacity decreases in patients with compromised liver function, but increases in patients with inflammation 11 . The inflammation that occurs in hepatitis A patients might explain why the BUN value was high.…”
Section: Discussionmentioning
confidence: 99%